Breaking the mobility–stability dichotomy in organic semiconductors through adaptive surface doping - Zhaofeng Wang; Xianshuo Wu; Siyuan Zhang; Shuyuan Yang; Pichao Gao; Panhui Huang; Yanling Xiao; Xianfeng Shen; Ximeng Yao; Dong Zeng; Jiansheng Jie; Yecheng Zhou; et al. (Proceedings of the National Academy of Sciences, 2025)
Organic semiconductors (OSCs) are pivotal for next-generation flexible electronics but are limited by an intrinsic trade-off between mobility and stability. We introduce adaptive surface doping (ASD), an innovative strategy to overcome this dichotomy in OSCs. ASD's adaptive mechanism accommodates a broad range of dopant concentrations, optimally passivating trap states as needed. This approach significantly lowers the trap energy level from 84 meV to 14 meV above the valence band edge, promoting a transition from hopping to band-like transport mechanisms. ASD boosts carrier mobility by over 60%, reaching up to 30.7 cm 2 V −1 s −1 , while extending the extrapolated operational lifetime of treated devices beyond 57.5 y. This breakthrough sets a standard in organic electronics, positioning ASD as a powerful method for simultaneously enhancing performance and stability in OSC devices.